PENERAPAN METODE 5S UNTUK MEMINIMASI DOWNTIME PADA PROSES GANTI ORDER DI PT. XYZ DENGAN PENDEKATAN LEAN MANUFACTURING - Haris Sandi Yudha; Alfi Febrizal; Agung Widarman; Muhammad Adam Yanuar (Jurnal Teknologika, 2023)
PT. XYZ is a company engaged in the plastic packaging (Flexible Packaging) industry in Indonesia and has customers from national to international levels. The large demand for plastic packaging requires companies to be able to meet every customer request. This large number of requests has an impact on the many types of products that must be fulfilled by the company, resulting in increased downtime during the change order process, especially on printing machines. With the lean manufacturing approach, there is a 5S method (seiri, seiton, seiso, seiketsu and shitsuke) as a way of creating and maintaining a quality work environment. After making observations, it is known that there are several activities that can be categorized as waste in the product replacement process, including waiting time, defects, excessive transportation and unnecessary motion. After processing with the 5S method, an improvement plan is made. At the Seiri stage, the improvements that must be made are by giving Red Tags, for the Seiton stage, the improvements are moving the preparation area and placing ink cans. At the Seiso stage, the improvements needed to make checksheets and layouts were made, at the Seiketsu stage, improvements were made to work instructions and making 5S posters, and finally, at the Shitsuke stage, training and outreach were carried out as well as periodic evaluations.